Do dietary buffers improve growth performance or nutrient digestibility or decrease stomach ulcers in finishing pigs? - K J Wondra; Robert H Hines; Joe D Hancock; Keith C Behnke (Kansas Agricultural Experiment Station Research Reports, 1993)
The effects of supplemental buffers in finely ground diets were determined in two experiments. In Exp. 1, 128 pigs (123 lb average initial body wt) were fed a cornsoybean meal-based diet (488 Î¼m mean particle size for corn) for 66 d. Treatments were a control and 1, 2, or 3% added sodium bicarbonate (NaHCO3). Average daily gain, dressing percentage, and plasma urea N concentration decreased as the concentration of NaHCO3 in the diet was increased. However, the reduction in average daily gain occurred only at the 2 and 3% additions. Feed intake, feed/gain, backfat thickness, stomach ulceration score, stomach keratinization score, and blood gases (pH and HCO3) were not affected by treatment. In Exp. 2, 120 pigs (121 lb average initial body wt) were fed a pelleted wheat-soybean meal-based diet (355 Î¼m mean particle size for the wheat) during a 64-d growth assay. Treatments were: 1) control; 2) 1% added NaHCO3; and 3) 1% added potassium bicarbonate (KHCO3). Average daily gain, feed intake, feed/gain, backfat thickness, stomach keratinization score, plasma urea N concentration, and digestibilities of dry matter and nitrogen were not affected by treatment. However, addition of NaHCO3 and KHCO3 tended to decrease the incidence of ulcers and increased the digestibility of gross energy. These data indicate that a 1% addition of either NaHCO3 or KHCO3 may help to reduce the severity of gastric ulcers in finishing pigs without adversely affecting growth performance or nutrient digestibility.; Swine Day, Manhattan, KS, November 18,1993
Keywords: Swine day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-194-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 695; Swine; Finishing; Stomach; Buffers; Particle size